Determinan Pertumbuhan Ekonomi Dan Pembangunan Modal Manusia Di Pulau Sumatera - Gulo, Tolo; Aimon, Hasdi (Universitas Negeri Padang, 2024)
This study aims to determine the extent of the influence of capital expenditure, domestic investment, government expenditure in education sector on economic growth on the island of Sumatra. As well as to determine the extent of the influence of government spending on education and health, population and economic growth on human capital on the island of Sumatra. The data used in this study is panel data which is a combination of time series from 2017-2022 and cross section in 10 provinces on the island of Sumatra. This study uses simultaneous equation analysis with the two state least square (2SLS) method. This study found that (1) simultaneously the variables of capital expenditure, domestic investment and government expenditure in the education sector have a significant effect on economic growth on the island of Sumatra. (2) Government expenditure in the education and health sector, population and economic growth have a significant effect on human capital on the island of Sumatra.